Evaluation of the ASN Talent Management Policy: A Case Study of the Surabaya City Education Office Based on the Mayor Regulation - Nur Arisah; Filda Putri Alis; Niken Ade Herlina (Sustainable Human Capital Development Journal, 2026)
Civil servant (ASN) talent management serves as a strategic instrument in bureaucratic reform, ensuring the provision of competent and professional human resources within local government. This study assesses the implementation of the ASN Talent Management Policy, as outlined in Surabaya Mayoral Regulation No. 30 of 2021, within the Surabaya City Education Office. Employing a qualitative case study approach, data were gathered through interviews and document analysis, subsequently analyzed using the CIPP (Context, Input, Process, Product) evaluation model. The findings reveal that the policy facilitates competency development, succession planning, and a merit-based career system. Nevertheless, challenges persist, including a top-down selection process, training that may not always align with job requirements, and administrative monitoring. Despite these limitations, the policy has yielded positive outcomes, such as talent pools, competency mapping, and enhanced employee competencies. The findings underscore the imperative of bolstering competency-based training and outcome-oriented evaluation to enhance the effectiveness of talent management.